2022
DOI: 10.3390/pathogens11030360
|View full text |Cite
|
Sign up to set email alerts
|

Subgingival Periopathogens Assessment and Clinical Periodontal Evaluation of Gastric Cancer Patients—A Cross Sectional Pilot Study

Abstract: Oral microbiota have shown a higher bacterial diversity in patients with cancers of the digestive tract, with higher levels of periopathogens. Recent studies have shown that Fusobacterium links to gastro-intestinal neoplastic tissue and accelerates its progression, as well as worsening patient outcome. The present pilot study was carried out between February and December 2020 to evaluate the possible association between the abundance of some periopathogens (Fusobacterium nucleatum, Porphyromonas gingivalis, Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…In addition to the presented research directions, there are still a few national and international scholars who have focused mostly on the relationship between periodontal disease and microorganisms, which in turn in uence oral carcinogenesis [21][22][23]. In Nicolae's study, the strong correlation between tumor size and all periodontal parameters, as well as with Clostridium nucleatum, may indicate a positive correlation between periodontal disease and the in uence of surrounding bacterial pathogens in the process of tumorigenesis [3]. Many studies have shown a positive correlation between periodontal disease and oral cancer, but the available evidence is insu cient to draw reliable conclusions [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the presented research directions, there are still a few national and international scholars who have focused mostly on the relationship between periodontal disease and microorganisms, which in turn in uence oral carcinogenesis [21][22][23]. In Nicolae's study, the strong correlation between tumor size and all periodontal parameters, as well as with Clostridium nucleatum, may indicate a positive correlation between periodontal disease and the in uence of surrounding bacterial pathogens in the process of tumorigenesis [3]. Many studies have shown a positive correlation between periodontal disease and oral cancer, but the available evidence is insu cient to draw reliable conclusions [24].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an increasing number of studies have shown that periodontal disease is closely associated with malignant tumors (genitour, pancreatic cancer, pharyngeal cancer, colon cancer and hepatocellular carcinoma) [1][2][3][4][5][6], and the relationship between periodontal disease and oral-maxillofacial-head and neck tumors has received increasing attention [7][8][9]. However, whether periodontitis induces the occurrence of oral cancer or whether the occurrence of oral cancer leads to the development of periodontitis is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial communities associated with cancer may be important for diagnosis and prognosis and future studies are needed for a better understanding of the dysbiotic tissue microbiome [ 81 ]. A previous research study found oral pathogens such as Fusobacterium nucleatum , Porphyromonas gingivalis , Treponema denticola , and Tannerella forsythia to be associated with gastric cancer [ 82 ]. F. nucleatum followed by T. forsythia were the most abundant bacteria associated with gastric cancers [ 82 ].…”
Section: Periodontitis Associated With Other Systemic Diseasesmentioning
confidence: 99%
“…A previous research study found oral pathogens such as Fusobacterium nucleatum , Porphyromonas gingivalis , Treponema denticola , and Tannerella forsythia to be associated with gastric cancer [ 82 ]. F. nucleatum followed by T. forsythia were the most abundant bacteria associated with gastric cancers [ 82 ]. Certain types of human oral bacteria, such as F. nucleatum or bacteroides, have also been reported to be associated with periodontitis, appendicitis, and colorectal cancer [ 83 ].…”
Section: Periodontitis Associated With Other Systemic Diseasesmentioning
confidence: 99%
“…A case-control study showed that F. nucleatum increased cancer risk factors [ 43 ]. Some researchers evaluated the possible association between the abundance of some periopathogens in the subgingival plaque and periodontal status and the characteristics of gastric cancer, and the results showed that the most abundant bacteria were F. nucleatum followed by T. forsythia in all groups [ 44 ]. Moreover, others also found that F. nucleatum -positive GC patients had significantly worse overall survival (OS) than the control group [ 45 ].…”
Section: Relationships Between F Nucleatum and Mal...mentioning
confidence: 99%